KRAS NF-κB is involved in the development of zinc resistance and reduced curability in prostate cancer - Holubova, Monika; Axmanova, Martina; Gumulec, Jaromir; Raudenska, Martina; Sztalmachova, Marketa; Babula, Petr; Adam, Vojtech; Kizek, Rene; Masarik, Michal (Metallomics, 2014)
Zinc(II) ions are important components of many proteins and are involved in numerous cellular processes such as apoptosis or drug resistance. Prostate cancer has a unique relationship with zinc(II) ions. However, the relationship was examined only in short-term zinc(II) treatments. Therefore, the aim of this study was to create zinc-resistant prostatic cell lines at various stages of the disease (22Rv1 and PC-3) and a normal prostate epithelium (PNT1A) using a long-term zinc exposure. Consequently, the expression profile of the following genes was analyzed: BAX, Bcl-2, Beclin-1, CFLAR, HIF1α, KRAS, mTOR, MT1A, MT2A, NF-κB1, p53, survivin, ZIP1, ZnT-1. The resistance was verified using the MTT test; on average a 1.35-fold lower zinc(II) toxicity (higher IC50) was determined in zinc(II)-resistant cells. The associated resistance to cisplatin was also determined; IC50 for cisplatin was 1.52-fold higher. With regard to the gene expression profiles, our results indicate that differential mechanisms participate in the short-term zinc toxicity regulation and long-term resistance; the short-term treatment was associated with MT2A (p < 0.001), ZnT-1 (p < 0.001), and MT1A (p < 0.03) and the long-term resistance was associated particularly with NF-κB1 (p < 0.001), CFLAR (p < 0.001), KRAS (p < 0.001), p53 (p < 0.002), survivin (p = 0.02), ZIP1 (p = 0.002), BAX (p = 0.005), and HIF1α (p = 0.05). Therefore, the KRAS-PI3K-NF-κB pathway is expected to play a crucial role in the regulation of zinc resistance. In summary, compared to previous studies, identical mechanisms of resistance were demonstrated on multiple cell lines, both non-tumor and tumorous, derived both from primary and advanced secondary sites.
Keywords: Transcriptome; Drug Resistance, Neoplasm; buněčné linie; Zinc; Male; Gene Expression Regulation, Neoplastic; nádorové buněčné linie; 1-fosfatidylinositol-3-kinasa; Cell Line, Tumor; apoptóza; NF-kappa B; lidé; Humans; Inhibitory Concentration 50; viabilita buněk; chemorezistence; inhibiční koncentrace 50; zinek; Prostatic Neoplasms; Apoptosis; transkriptom; mužské pohlaví; nádory prostaty; prostata; cisplatina; Cisplatin; Cell Survival; regulace genové exprese u nádorů; Cell Line; Prostate; Phosphatidylinositol 3-Kinase